The effect of 24-hour presence of emergency medicine specialists on the performance of emergency department of Shahid Bahonar hospital, Kerman/Iran, 2013 - Mohammad Reza Amiresmaili (Journal of Emergency Practice and Trauma, 2015)
Introduction: Emergency department is the most important part of a hospital and it seems that 24-hour presence of emergency medicine specialist can be effective in improving the performance of this ward. Therefore, the present study was performed with the aim of studying the effect of 24-hour presence of emergency medicine specialists in the emergency department of Shahid Bahonar hospital, Kerman/Iran. Methods: In this mixed methods study, data collection was done through studying various related documents and semi-structured interview. Data analysis was performed using descriptive statistics and qualitative content analysis. Results: The presence of emergency medicine specialists resulted in a decrease in waiting time, hospital’s revenue growth, increase in number of requested laboratory tests, improvement of decision-making for patients and decrease of first 24-hour mortality rate. Economic benefits, improvement of the quality of services and emergency department management were among qualitative results of the present study. Conclusion: In whole, 24-hour presence of emergency medicine specialists in the emergency department of Kerman Shahid Bahonar hospital has been effective in improving the performance and quality of services. Keywords